Influence of seasonal and geographic variation on the anti-HSV-1 properties and chlorogenic acids content of Helichrysum aureonitens Sch. Bip - Adeosun, Wilson Bamise; More, Garland K.; Steenkamp, Paul; Prinsloo, Gerhard (Frontiers in Molecular Biosciences, 2022)
Pharmacological studies conducted in the past revealed the potential source of medicinal plants in the development of novel medicines. The phenolic content of medicinal plants containing chlorogenic acids (CGA) has been linked to a variety of therapeutic effects, especially antiviral activity. Helichrysum aureonitens is a medicinal plant which has been reported to contain chlorogenic acids compounds and has also shown antiviral activities against a number of virus species including Herpes Simplex Virus-1 (HSV-1). In this study, the aim was to determine both the influence of seasonal variation and locality on the antiviral properties of H. aureonitens. Since chlorogenic acids have been reported as potent antiviral compounds, these compounds were targeted to determine the effects of locality and season on the chlorogenic acid profile, and subsequent antiviral activity. The ultra-performance liquid chromatography-quadrupole time-of-flight mass spectroscopy (UPLC-qTOF-MS) was employed to determine the metabolic profile variations of three derivatives of chlorogenic acids-caffeoylquinic acid (CQA), dicaffeoylquinic acid (DCQA) and tricaffeoylquinic acid (TCQA) in the harvested plants growing in two diverse geographical climates and two different seasons (spring and autumn). Using the cytopathic effect (CPE) reduction approach, twenty-six samples of the plants’ leaves and stems collected during spring and autumn at Telperion nature reserve in Mpumalanga and Wakefield farm, Midlands in KwaZulu-Natal region of South Africa were evaluated for anti-HSV activity. The MTT assay was used for the cytotoxicity evaluation of the extracts prior to antiviral determination. Seventeen (mostly spring collections) of the twenty-six extracts examined were found to have considerable anti-HSV activity, as measured by a reduction in tissue culture infectious dose (TCID50) of less than 105. The UPLC-qTOF-MS result revealed that dicaffeoylquinic acid (DCQA) is the most abundant, with higher concentrations in both regions and seasons. 3-CQA was also shown to be the most abundant isomer of caffeoylquinic acid in this investigation.